Trust in public institutions over the business cycle - Betsey Stevenson; Justin Wolfers (Institute for the Study of Labor (IZA), 2011)
We document that trust in public institutions and particularly trust in banks, business and government has declined over recent years. U.S. time series evidence suggests that this partly reflects the pro-cyclical nature of trust in institutions. Cross-country comparisons reveal a clear legacy of the Great Recession, and those countries whose unemployment grew the most suffered the biggest loss in confidence in institutions, particularly in trust in government and the financial sector. Finally, analysis of several repeated cross-sections of confidence within U.S. states yields similar qualitative patterns, but much smaller magnitudes in response to state-specific shocks.
urn:nbn:de:101:1-201104133920
Keywords: D72; E32; E65; K0; O4; P52; Z13; 330; trust; institutions; confidence; survey data; congress; banks; big business; media; courts; Vertrauen; Institutionelle Infrastruktur; Konjunktur; Bank; Großunternehmen; Regierung; Kommunikationsmedien; USA